Volatile Constituents of Aerial Parts of Euphorbia aellenii Rech.f. and E. microsciadea Boiss. from Iran: Volatile constituents of Euphorbia spp. - Suleiman Afsharypuor; Mustafa Ghanadian; Abdul Majid Ayatollahi; Muhammad Iqbal Choudhary (Iranian Journal of Pharmaceutical Sciences, 2010)
The volatile constituents of aerial parts of Euphorbia aellenii Rech.f. and E.microsciadea Boiss. were analyzed by gas chromatography (GC) and GC-mass spectrometry (MS) methods. The main volatile constituents of E. aellenii were phytol isomer (47.3%), camphene (31.9%) and caryophyllene oxide (20.6%), while the major volatile components of E. microsciadea were trans-anethole (74.5%), limonene (7.7%), hexadecanoic acid (6.8%), fenchone (6.0%) and phytol isomer (4.9%).